SAT0488 Organ involvement and ild progression in scleroderma patients with anti-topoisomerase i specificity and limited cutaneous form. (12th June 2018) - Zanatta, E.; Polito, P.; Ometto, F.; Felicetti, M.; Tonello, M.; Scanu, A.; Punzi, L.; Cozzi, F.
Abstract : Background: The great variability of clinical manifestations in systemic sclerosis (SSc) yields the need of defining prevalence and progression of organ involvement in the different subsets of the disease. Despite the classical association between anti-topoisomerase-I (SCl70) positivity with diffuse cutaneous SSc (dSSc), and anti-centromere (ACA) with limited cutaneous SSc (lSSc), a population of patients with antiScl70 and lSSc has been described. 1 Interstitial lung disease (ILD) is nowadays the leading cause of mortality in SSc; its progression can range from a self-limiting form to a rapidly progressive lung involvement, despite immunosuppressive treatment. Objectives: The aim of our study was to evaluate the prevalence of different organ involvement in three groups of patients: ACA-lSSc, SCl70-dSSc e SCl70-lSSc. Our second endpoint was to investigate possible differences in ILD onset and progression between SCl70-lSsc and SCl70-dSSc patients. Methods: Consecutive 260 patients attending the Rheumatology Unit of Padova University of Padova were included and retrospectively evaluated. Clinical, biochemical and functional parameters concerning pulmonary, cardiac and articular involvement were collected in all patients, with an average follow-up time of 15 years. As for lung involvement, spirometric indices (FVC e DLCO) and HRCT at ILD onset and at last follow up were considered (median ILD duration 8 years 4, 12 ). Time between SSc onset and ILD first evidence was defined as "scleroderma free ILD". ILD grading was determined according to Kazerooni score. ILD progression was defined as either an HRCT score worsening of at least 2 points, or as a significant progression of spirometric indices (10% and 15% for FVC and DLCO respectively). 2 Results: 150 patients with ACA-lSSc, 58 with SCl70-dSSc and 52 with SCl70-lSS were included in the study. SCl70-lSSc patients presented more often with pulmonary and articular involvement with respect to ACA-lSSc patients (50% vs 6.9% and 42.9% vs 23.6% respectively), and less often compared to SCl70-dSSc. In SCl70-lSSc, cardiac and gastrointestinal involvement, BEV and digital ulcers were less prevalent with respect to SCl70-dSSc (p<0.05). SCl70-lSSc patient had a longer "scleroderma free-ILD" compared to SCl70-dSSc. At ILD onset pulmonary function was worse in SCl70-dSSc group than in SCl70-lSSc group (p=0.02 e p=0.009 for FVC e DLCO respectively), even in the absence of a significant difference between HRCT scores (12.73±5.25 vs 10.25±4.93, p=0.284). Total ILD progression was significantly higher in SCl70-dSSc (p<00001). Conclusions: Our study shows that SCl70-lSSc patients appeared to have a different prevalence of targeted organ involvement and ILD progression with respect to both SCl70-dSSc and ACA-lSSc. Since the correct classification of SSc patients is extremely important in view of a tailored treatment, our data suggest that it could be worth to identify patients with SCl70 and limited cutaneous form as a different and specific subset. References: [1] Steen VD. Autoantibodies in systemic sclerosis. Semin Arthritis Rheum2005;35:35–42. [2] Bosello S, et al. Long-term efficacy of B cell depletion therapy on lung and skin involvement in diffuse systemic sclerosis. Semin Arthritis Rheum2015, 44:428–436. Disclosure of Interest: None declared